3(x-6)+5x=-82

Simple and best practice solution for 3(x-6)+5x=-82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-6)+5x=-82 equation:



3(x-6)+5x=-82
We move all terms to the left:
3(x-6)+5x-(-82)=0
We add all the numbers together, and all the variables
5x+3(x-6)+82=0
We multiply parentheses
5x+3x-18+82=0
We add all the numbers together, and all the variables
8x+64=0
We move all terms containing x to the left, all other terms to the right
8x=-64
x=-64/8
x=-8

See similar equations:

| k+3/5-k-3/3=2/5 | | 2x+13=9x-1 | | –17=–2+5x | | 7(1-3k)+4k=109 | | -4x()=8 | | x+3=18 | | -6(10+7x)=-564 | | 2x–9=-3x+21 | | 7d-2=5d+2 | | -4(1-4p)-4p=92 | | 29x-6=168 | | 2{5x-3}=14 | | -6x-47=28-x | | 2=h2 | | k+3/5-k-3/3=2 | | −5x+8=63 | | 5(3b+7)=155 | | 6x+42=8x+50 | | x+(x÷2)+(x÷4)=1,225 | | 7(1-3k)+4k=109k= | | 0x+14=x+68 | | 7(-9-2x)=105 | | i-14=3I-60-42 | | 7w-6=3w3 | | 6x+5(x+8)=95 | | 5/2x+2(3/4x)=5 | | 1=q+12 | | 2(−8+a)=−38 | | -6=5x-17÷3 | | 7c-5c4=4c-10 | | 4/x=6/3x | | 3(8r−3)+1=−1283×8r−3×3+1=−12824r−9+1=−12824r−8=−128+8=+824r=−120÷24=÷24r=−5 |

Equations solver categories